Predictive density construction and accuracy testing with multiple possibly misspecified diffusion models - Valentina Corradi; Norman Swanson (Rutgers University, Department of Economics, 2011)
This paper develops tests for comparing the accuracy of predictive densities derived from (possibly misspecified) diffusion models. In particular, we first outline a simple simulation-based framework for constructing predictive densities for one-factor and stochastic volatility models. Then, we construct accuracy assessment tests that are in the spirit of Diebold and Mariano (1995) and White (2000). In order to establish the asymptotic properties of our tests, we also develop a recursive variant of the nonparametric simulated maximum likelihood estimator of Fermanian and Salanié (2004). In an empirical illustration, the predictive densities from several models of the one-month federal funds rates are compared.
Keywords: C22; C51; 330; block bootstrap; diffusion processes; jumps; nonparametric simulated quasi maximum likelihood; parameter estimation error; recursive estimation; stochastic volatility; Prognoseverfahren; Zeitreihenanalyse; Modellierung; Schätztheorie; Theorie